Accounting standards complexity, audit fees and financial analyst forecasts in Australia : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Accounting at Massey University, Albany, New Zealand - Miah, Muhammad Shahin (Massey University, 2017)
While the beneficial effects of International Financial Reporting Standards (IFRS) on financial reporting quality, cost of capital, cross-country investment, corporate decision making and governance are well studied in the literature, there is relatively little research on the cost side of IFRS adoption and its impact on users. This thesis contributes by investigating the impact of IFRS complexity on two important groups of users of financial reports namely auditors and financial analysts. The hypotheses are built on the premise that principles-based standards are more complex than rules-based standards. This study examines the relationships between IFRS complexity, audit fees, and analyst forecast properties. IFRS is likely to require more of auditors in terms of professional expertise, time and effort, hence resulting in higher audit fees. Financial analysts may be similarly affected by the complexity of IFRS resulting in less accurate forecasts on key financial components. This thesis measures IFRS complexity based on individual IFRS standards specifically identified as having higher levels of complexity. Scores are then calculated to indicate the difference between these IFRS standards and their equivalent previous domestic accounting standards. The degree of complexity is also measured at aggregate level to indicate an overall complexity impact based on the combined score for all identified 'complex' IFRS standards. Findings indicate that aggregate IFRS complexity is positively and significantly associated with audit fees but that specific IFRS standards are identifiable as being paiticularly complex, hence explaining much of the positive relationship with audit fees. The results also reveal that the incremental effect of IFRS complexity on audit fees is more pronounced when finns are audited by city-level industly specialists as opposed to those audited by nonindustly specialists. Furthermore, IFRS complexity is found to have a positive and significant association with analyst forecast properties (forecast errors, forecast dispersion, and forecast revision). Surprisingly some of the standards identified as being more complex for auditors (i.e., driving higher audit fees) do not appear similarly complex in relation to financial analyst forecast properties. Finally, this thesis investigates the moderating role of high quality audits (proxied by industry specialist auditors) on complexity and analyst forecast properties and finds that forecast errors decrease for firms which are exposed to higher levels of IFRS complexity if they are audited by city-level industly specialists. This study provides important insights for regulator regarding the complexity of specific IFRS standards. Findings may also be of benefit to countries which are in the process of adopting IFRS or planning to do so.
Keywords: Accounting; Standards; Financial statements; Auditors; Fees; Investment analysis; Australia; International Financial Reporting Standards; Research Subject Categories::SOCIAL SCIENCES::Business and economics